Thermal-annealing effects on energy level alignment at organic heterojunctions and corresponding voltage losses in all-polymer solar cells. (June 2020) - Wang, Chuanfei; Moro, Fabrizio; Ni, Shaofei; Zhang, Qilun; Pan, Guoxing; Yang, Jinpeng; Zhang, Fapei; Buyanova, Irina A.; Chen, Weimin M.; Liu, Xianjie; Fahlman, Mats
Abstract: Matched energy level alignment is a key requirement for efficient organic devices such as organic light-emitting diodes, photovoltaics, and field-effect transistors. The effect of thermal stress/annealing on energy level alignment and related properties of the devices are less discussed compared to the extensively explored effect on morphology and corresponding device performance. Here all polymer solar cells (all-PSCs) are employed to study thermal annealing effects on energy level alignment and the corresponding effect on the device properties of the all-PSCs. It is found that optimized energy level alignment can be achieved by thermal annealing. An interface dipole layer at the donor/acceptor interface is introduced by energy level realignment that assists charge generation by reducing geminate recombination so that the voltage loss is dramatically reduced, improving the performance of the all-PSCs. Graphical abstract: Image 1 Highlights: Energy levels of organic semiconductors can be changed by thermal annealing (stress). A change in energy levels can cause spontaneous integer charge transfer from polymer donor to acceptor. Ground state integer charge transfer will introduce an interface dipole layer at the donor-acceptor heterojunction. An interface dipole layer can enhance exciton-to-charge generation and decrease open circuit voltage losses.. The design rule for energy level matching holds for state-of-the-art efficient organic solar cell.